2022
DOI: 10.1016/j.isci.2021.103699
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immunogenicity two months after SARS-CoV-2 messenger RNA vaccines in patients with cancer

Abstract: Little is known on the long-lasting humoral response and the T cell activation induced by SARS-COV2 mRNA vaccines in patients with cancer. The study assessed the efficacy of the SARS-COV2 mRNA vaccines through measuring the seroconversion rate at pre-specified time points and the effect on the T cell immunity in patients with cancers. The study included 131 adult patients with solid or haematological cancer, who received SARS-COV2 mRNA vaccines. 96.2% of them exhibited adequate antibody response to the SARS-CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Thus, our data further confirm the efficacy of the vaccine in triggering the cellular immune responses in patients with cancer in agreement with a study by Bordry et al. ( 18 ). Specific humoral responses were detected in all cancer patients after the second dose of the mRNA vaccine, in line with other studies showing that the majority of cancer patients are able to mount specific antibody responses to SARS-CoV-2 vaccines ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our data further confirm the efficacy of the vaccine in triggering the cellular immune responses in patients with cancer in agreement with a study by Bordry et al. ( 18 ). Specific humoral responses were detected in all cancer patients after the second dose of the mRNA vaccine, in line with other studies showing that the majority of cancer patients are able to mount specific antibody responses to SARS-CoV-2 vaccines ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, little is known regarding the long-term humoral and cellular responses triggered by SARS-CoV-2 mRNA vaccines in solid cancer patients after repeated booster doses. The scarce existing evidence points towards an enhanced humoral and T-cell response after the second dose ( 18 ) as well as an enhanced humoral response after an additional booster ( 19 ), although the latter seems of lower intensity compared to healthy subjects ( 20 ). Moreover, there is scant data concerning cell-mediated immunity and the potential exhaustion of T-lymphocytes in the event of repeated booster doses of SARS-CoV-2 vaccine in this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, oncologic treatments received during vaccination have been shown to have an impact on antibody titers, with lower titers for patients on cytotoxic chemotherapy or monoclonal antibodies and with a very low rate of seroconversion, especially in those who received anti-CD20 rituximab in the 6 months prior to vaccination. Hematopoietic malignancies, compared with patients with solid tumors, were less likely to develop a high antibody response [ 4 , 5 ]. In this study, receiving chemotherapy at the time of vaccination was found to be associated with a higher risk of having a “poor” response with an odds ratio (OR) of 0.16 (95% CI: 0.0–0.85).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have been performed to investigate the immunogenicity of SARS-CoV-2 vaccines in immunocompromised populations. Compared to the general population, people living with HIV (PLWH) and patients with solid tumors showed similar seroconversion rates (90–95%) after two and three doses of mRNA vaccines [ 4 , 5 , 6 , 7 ]. However, patients receiving cytotoxic chemotherapy or monoclonal antibodies [ 4 , 5 ] had lower antibody titers when compared to patients not receiving these oncologic treatments [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation